Second harmonic generation in monolithic gallium phosphide metasurfaces - Yang Muyi; Weissflog Maximilian A.; Fedorova Zlata; Barreda Angela I.; Börner Stefan; Eilenberger Falk; Pertsch Thomas; Staude Isabelle (Nanophotonics)
Gallium phosphide (GaP) offers unique opportunities for nonlinear and quantum nanophotonics due to its wide optical transparency range, high second-order nonlinear susceptibility, and the possibility to tailor the nonlinear response by a suitable choice of crystal orientation. However, the availability of single crystalline thin films of GaP on low index substrates, as typically required for nonlinear dielectric metasurfaces, is limited. Here we designed and experimentally realized monolithic GaP metasurfaces for enhanced and tailored second harmonic generation (SHG). We fabricated the metasurfaces from bulk (110) GaP wafers using electron-beam lithography and an optimized inductively coupled plasma etching process without a hard mask. SHG measurements showed a high NIR-to-visible conversion efficiency reaching up to 10−5, at the same level as typical values for thin-film-based metasurface designs based on III–V semiconductors. Furthermore, using nonlinear back-focal plane imaging, we showed that a significant fraction of the second harmonic was emitted into the zeroth diffraction order along the optical axis. Our results demonstrate that monolithic GaP metasurfaces are a simple and broadly accessible alternative to corresponding thin film designs for many applications in nonlinear nanophotonics.